Light scattering by surface waves on a vertical layer of liquid toluene - Fröba, Andreas Paul; Will, Stefan; Leipertz, Alfred (Applied Optics, 1997)
It is demonstrated that light scattering from surface waves on a vertical Liquid layer can be used for the determination of surface tension and kinematic viscosity of the liquid under investigation. In contrast to usual approaches of surface Light scattering, a setup is described that enables measurements with the same setup as that with experiments for the determination of other thermophysical properties by light scattering from bulk fluids and without an imposed grating or seed particles. The experiments rely on a heterodyne detection scheme and a signal analysis by photon correlation spectroscopy. First results are presented for toluene over a temperature range from 323 to 483 K at saturation conditions. (C) 1997 Optical Society of America.
Keywords: surface light scattering; viscosity; surface tension; toluene